Drug rash with eosinophilia and systemic symptoms and severe renal injury induced by proton pump inhibitor therapy: A case report. Issue 42 (16th October 2020) - He, Qien; Ying, Guanghui; Fei, Xiapei; Zha, Chenqin; Chen, Zhaogui; Bao, Yishu; Long, Jiaorong; Wang, Zhujun; He, Xuelin; Xia, Min
Abstract: Introduction: Proton pump inhibitors (PPIs) are widely prescribed and generally well tolerated but can rarely cause severe allergic reactions, such as drug rash with eosinophilia and systemic symptoms (DRESS). We report a case of DRESS and renal injury induced by PPIs, and describe the therapeutic process. Patient concerns: The patient was a 66-year-old female who complained of fever, pruritus, desquamation, erythema multiforme, and anuria caused by omeprazole taken for 2 weeks to treat abdominal distention. Diagnosis: The clinical history revealed a similar episode of PPI-induced fever, eosinophilia, and acute kidney injury more than 1 year ago. The present laboratory tests revealed eosinophilia and oliguric renal failure. The renal biopsy was performed subsequently and proved the diagnosis of PPI-induced DRESS. Interventions: After the suspected diagnosis of PPI-induced DRESS, omeprazole was discontinued and methylprednisolone infusion (40 mg qd) was initiated. Because of oliguric renal failure, the patient received intermittent hemodialysis. Outcomes: The patient initially responded to omeprazole discontinuation, hemodialysis, and glucocorticoids but later died from severe infection during the tapering of glucocorticoid therapy. Conclusion: Clinicians should remain on high alert for potential life-threatening complications when prescribing PPIs. If unexplained renal injury develops in a patient taking a PPI, renal biopsy may help in identifying the pathogenesis and might facilitate timely intervention.